2007
DOI: 10.1111/j.1939-1676.2007.tb01957.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Immunotherapy of Feline Fibrosarcoma with Recombinant Feline Interferon‐ω

Abstract: Background: Recombinant feline interferon-v (rFeIFN-v) was tested as a treatment option for cats with fibrosarcoma to assess safety and feasibility.Hypothesis: Treatment with rFeIFN-v in cats with fibrosarcoma is safe and feasible. Animals: Twenty domestic cats. Methods:In an open-labeled uncontrolled clinical trial 12 injections of 1 3 10 6 U/kg rFeIFN-v were administered over a 5-week period: the 1st through 4th injections were given intratumorally, and the 5th through 12th injections were administered subcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…Currently, few successful treatments for fibrosarcoma have been reported in cats, although treatment of feline fibrosarcoma with rFeIFN-ω has been demonstrated to be safe, well tolerated, and easily performed. A study by Hampel et al [103] revealed that rFeIFN-ω increased the expression of major histocompatibility I molecules on feline fibrosarcoma cells, while eosinophilia, neutropenia, and weight loss were remarkably reduced by rFeIFN-ω treatment. However, a placebo-controlled trial is needed.…”
Section: Fibrosarcomamentioning
confidence: 99%
“…Currently, few successful treatments for fibrosarcoma have been reported in cats, although treatment of feline fibrosarcoma with rFeIFN-ω has been demonstrated to be safe, well tolerated, and easily performed. A study by Hampel et al [103] revealed that rFeIFN-ω increased the expression of major histocompatibility I molecules on feline fibrosarcoma cells, while eosinophilia, neutropenia, and weight loss were remarkably reduced by rFeIFN-ω treatment. However, a placebo-controlled trial is needed.…”
Section: Fibrosarcomamentioning
confidence: 99%
“…The overall goal of these approaches is to induce and/or augment tumour specific immune responses and counteract suppressive cell subsets within the TME to create a permissive milieu for effective anti‐tumour immunity. Key approaches to achieve this include: activation of non‐specific innate immunity, 74,75,91‐107 administration of tumour vaccines and cytokines, 108‐113 monoclonal antibodies (mAbs) to target uniquely expressed or over‐expressed cell surface antigens and promote antibody dependent cell mediated cytotoxicity (ADCC) or block checkpoint molecules unleashing anti‐tumour immunity, 114 adoptive transfer of polyclonal or genetically modified T cells, and modulation of the TME to minimize immunosuppression 63,115 …”
Section: Veterinary Clinical Trialsmentioning
confidence: 99%
“…A ressecção cirúrgica do tumor deve alcançar 3-5 cm de margens laterais e duas camadas musculares ou osso como margem profunda (SCHERK et al, 2013;LADLOW, 2013 A imunoterapia adicional parece ter resultados promissores (HARTMANN et al, 2015). Um estudo utilizou interferon-ω felino para o tratamento de fibrossarcoma para avaliar sua segurança e viabilidade como uma opção de tratamento para gatos; foi considerado seguro e bem tolerado, porém ainda deve ser testado em um ensaio controlado com placebo para avaliar a eficácia no tratamento (HAMPEL et al, 2007). Kirpensteijn (2006) também cita que a utilização de gene da interleucina-2 pode promover menor recorrência do tumor associando à radioterapia e cirurgia.…”
Section: Introductionunclassified